STUDIES ON FOLLICULAR DEVELOPMENT AND OVARIAN STEROID PROFILE IN SEASONAL ANESTRUS GOATS - SARATH, T; MEHROTRA, S; ARUNMOZHI, N; AGARWAL, S K; HOQUE, M; HOQUE, UMASHANKAR (The Indian Journal of Animal Reproduction, 2023)
The present study was conducted with the objective to study the follicular growth and steroid profile in acyclicgoats. The seasonal anestrus goats (n=7} were selected on the basis of absence of estrus after buck parading. Allthe goats were subjected to twice in a week (Day 0(day of first scanning), 4, 8, 12, 16 and 20) ultrasonographicscanning of ovaries using real time 8-mode scanner equipped with 6.0 MHz linear array transducer to examinefollicular development. Follicles were counted, measured and classified as small (4.0mm). Blood samples were also collected through jugular venipuncture on the day of scanning forestimation ofestradiol and progesterone. Serum estradiol and progesterone were estimated by Radioimmunoassay(RIA). In the present study, there was no significant difference in different category of follicles and total follicularpopulation in anestrus goat indicating emergence of relatively constant number of follicles on different days ofobservation. There was no appreciable difference in the follicular diameter between different days of observation.Serum estrogen values did not differ significantly on different examination days in acyclic goats. Serum progesteronewas significantly low throughout study period.
Keywords: Follicular dynamics; Goat; Anestrus; Ultrasonography